Does a restrictive visitor arrangement on the NICU, due to the COVID-pandemic, have a negative impact on the parent-child bonding process? - van Loo, Anouk; Van Hoestenberghe, Marie-Rose (Belgian Journal of Paediatrics, 2023)
Background and objectives Due to the COVID-19 pandemic and the associated safety measures, visitor arrangements on the neonatal intensive care unit had to be drastically restricted. This single-centre prospective study investigated the influence of this restrictive visitor arrangement on parent-child bonding. Methods Thirty parental couples of neonates hospitalized in NICU were recruited. During restricted visitor policy only one parent at a time was allowed to visit and kangaroo the baby with a time restriction of 3 hours per day per parent. During non-restrictive policy there were no time restrictions for parental visits and parents were allowed to visit their baby simultaneously. Fourteen couples were recruited during restricted visitors policy in April 2020. Sixteen couples were recruited in the following period with non-restrictive policy. The couples filled in two questionnaires, the Dutch Postpartum Bonding Questionnaire and the Dutch Edinburgh Parental Depression Scale, at one week postpartum (T1) and at the child’s age of four months (T2). Result At T1 there was a significant (p= 0.019) lower Postpartum Bonding Questionnaire-score in the non-restrictive group, representing better parent-child bonding. This difference between these groups was not found at 4 months postnatally. Conclusion We suggest that restrictive visitor policy on the neonatal intensive care unit had a negative effect on early parent-child bonding. This shows the importance of an unlimited visitor policy. Little is known about long-term effects of parent-child bonding at specific ages, although some reports emphasize the importance of very early parent-child bonding. Further investigations are needed.